2005
DOI: 10.1017/s095026880500511x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between serological responses to Brucella suis and Yersinia enterocolitica serotype O[ratio ]9 after natural or experimental infection in pigs

Abstract: False-positive serological reactions (FPSR) due to infections with Yersinia enterocolitica serotype Oratio9 (YeOratio9) are a problem in tests for brucellosis. In the present study, FPSR in classical and novel tests for brucellosis following experimental infections of pigs with YeOratio9 were compared with responses of B. suis biovar 2-inoculated pigs. FPSR were limited to 2-9 weeks post-YeOratio9 inoculation, while B. suis-infected pigs were test-positive throughout the 21-week period of investigation. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…In our study, none of the isolates was ystB-positive. This result is similar to findings of other authors, who found that ail+ and ystA+ positive Y. enterocolitica strains are almost always ystB-negative (9,20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, none of the isolates was ystB-positive. This result is similar to findings of other authors, who found that ail+ and ystA+ positive Y. enterocolitica strains are almost always ystB-negative (9,20).…”
Section: Discussionsupporting
confidence: 92%
“…One of the most important problems which should be always taken into account is the possibility of cross reactions between Brucella sp. and Y. enterocolitica O:9, which are difficult to distinguish from specific anti-Brucella reactions (6,9,14,16,20,23). The study of Szulowski et al (19) presents that each year, in Poland, a very limited number of cattle is classified as positive for brucellosis and slaughtered, but Brucella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the data from the literature and our current and previous results we conclude that false positive serological reactions in porcine brucellosis serology are not unusual (Jungersen et al 2006, OIE Manual 2012 and clear guidelines for dealing with such cases should be created.…”
Section: Resultsmentioning
confidence: 71%
“…Detection of Y. enterocolitica O:9 in the herd with a high degree of probability confirms the reason of false positive reactions for brucellosis. Determining the presence of other serotypes of Y. enterocolitica in the herd, beside serotype O:9, is not surprising as there are no biological differences between the serotypes and their different distribution in the herd is possible (Jungersen et al 2006). Implementation of bacteriological examination for the presence of Y. enterocolitica O:9 and isolation of this bacteria provides very important information enabling proper interpretation of the results.…”
Section: Resultsmentioning
confidence: 99%
“…Zootec., v.65, n.5, p.1321-1328, 2013 (Organización..., 1986), não é recomendado para áreas de baixa prevalência (Motta et al, 2010), uma vez que apresenta alta sensibilidade e baixa especificidade, podendo ocorrer reações cruzadas com Yersinia enterocolitica e Brucella spp. (Jungersen et al, 2006). Na região Nordeste, resultados semelhantes foram obtidos em estudo conduzido em granjas de suínos na região metropolitana de Recife, onde apenas 2,4% dos animais foram positivos ao 2-ME (Ribeiro et al, 2000).…”
Section: Discussionunclassified